Sinais do transtorno do espectro autista de zero a 12 meses descritos em instrumentos e pesquisas aplicadas: um esboço de possíveis contingências envolvidas - Barbieri, Leticia (2021)
Currently, autism spectrum disorder (ASD) is one of the most common developmental disorders in school-age children, with impairments in areas of communication, socialization, and adaptive functioning. In the United States, the average age of diagnosis in children who were born in 2012 was 33 months. However, studies have demonstrated that the first behavioral signs can already be perceived in the first year of life (e.g., Szatmari et al., 2016) and that the age when the intervention begins has a direct correlation with the success of the treatment and the individual’s prognosis, although the signs in this stage of life are still little present in early screening instruments. The present study aimed to describe possibly involved contingencies in behaviors that are called here early behavioral signs of ASD, which may be present within the range of zero to 12 months of age, based on literature on behavior analysis and child development. A survey of the behavioral signs described in screening instruments and applied researches was carried out. Twelve behavioral signs were selected and described as possible predictors of ASD from zero to 12 months of age: visual contact, imitation, response to name, single-word understanding, babbling, communicative coordinations, social smile, anticipatory response, social game, head tilt reflex, response to sounds, exchange of look between stimulus. These signs were classified according to behavior analysis and child development literature into six behavior areas: pre-listener, listener, prespeech, social, motor and sensory. Have been described the antecedent condition under which the classes of responses involved in the signs could be evoked, what would these classes of responses be and the possible consequences involved